«Житіє Алексія Человѣка Божія» архієпископа Іоана Максимовича у контексті україно-польсько-російських літературних зв'язків - Журавльова, Світлана; Zhuravlova, Svitlana (Волинський національний університет імені Лесі Українки, 2008)
У статті здійснено компаративний аналіз вірша „Житіє Алексія Человiка Божія” із книги „Алфавит собранный, риѳмами сложенный…” архієпископа Іоана Максимовича та давньоруського тексту житія Олексія, чоловіка Божого, редакцій житія, створених Петром Скаргою, Арсенієм Греком, Лазарем Барановичем, Димитрієм Тупталом. The poems „Alexei’s the God’s Person Hagiography” by archbishop Joan Maksimovich in the Context of the Ukrainian, Polish and Russian Literary Relations. In the article the comparative analysis of the poem „Alexei’s the God’s Person Hagiography” from the book „The Alphabet Gathered and Arranged with the Rhyme” by Joan Maksimovich with the old Russian text of Alexei’s hagiography, with editions of it’s hagiography, created by Piotr Skarga, Arseny Greek, Lazar Baranovych, Dymytry Tuptalo is carried out.
The poems „Alexei’s the God’s Person Hagiography” by archbishop Joan Maksimovich in the Context of the Ukrainian, Polish and Russian Literary Relations
Keywords: житіє; hagiography; бароко; baroque; впливи; influences; вірш; poem; oбробка; procces